Effect of Nitrogen Fertilizer Applications on Nitrogen Remobilization and Grain Yield in Soybean (Glycine max [L] Merril) in the Savelugu-Nanton Municipality in Northern Region of Ghana - John Bokaligidi Lambon; Joseph Sarkodie- Addo; James Mantent Kombiok (Turkish Journal of Agriculture: Food Science and Technology)
Two experiments were conducted in the Savelugu-Nanton Municipality of the Northern Region of Ghana in 2012 and 2013 to assess the effect of N fertilizer on growth, N remobilization and grain yield of three local varieties of soybean (Glycine max [L] Merill). The experiments were a 3 x 4 factorial laid in Randomized Complete Block Design (RCBD) with four replications. Factor A was soybean varieties (Jenguma, Quarshie, Ahotor); Factor B was 0, 15, 30 and 45 kg N ha-1. The experimental fields were planted manually on the flat by drilling and later thinned to 2 plants hill-1 at 0.50 m × 0.10 m with a population of about 400 000 plants ha-1. Growth and yield parameters measured were plant height, nodule number plant-1, nodule dry weight plant-1, percent nodule effectiveness, number of pods plant-1, number of seeds pod-1, 100 seed weight, harvest index and grain yield. The results showed that the control recorded lower figures in all growth parameters. Nitrogen remobilization was also observed in all plots, which indicate that soybean needs greater levels of N during grain filling. Again, N remobilization and soybean yield were highest in the 45 kg N ha-1 treatment compared to the other treatments. However, considering the overall yields, farmers in the study area should be advised to adopt starter N fertilization of soybean for higher yields as the soils are highly degraded in soil fertility.